Evaluasi Manajemen Strategi Pada Dinas Tenaga Kerja Kota Bandung Provinsi Jawa Barat (Institut Pemerintahan Dalam Negeri, 2019)
Abstract The Manpower Office of the city of Bandung is a regional organization which is tasked with carrying out some of the governmental affairs based on the principle of autonomy and assistance tasks in the field of labor, and has the functions listed in the regional regulation number 05 of 2013 concerning the second change of the Bandung City Regulation No. 13 of 2007, about the Formation and Structure of the Bandung Regional Office. Reporting from the website of the Bandung City Manpower Office, there were 7,343 registered job seekers, and 1,897 available vacancies. Of the total 1,897 job vacancies the number of placements that have been revised by the Bandung City Manpower Office is 1,469. When viewed from the data, there is a high gap between the number of jobs available and the number of work needs. On the other hand, there are a number of job openings that are not optimally distributed with the number of job seekers. This is certainly the basis for the Bandung City Manpower Office to immediately have strategic management to overcome these problems. With the management strategy of the Bandung City Manpower Office, can determine the direction and objectives of HR management in the city of Bandung so that it can be realized with optimal work needs with job seekers as well as creating human resources in the city of Bandung who are quality and superior in order to answer the challenges in today's globalization era. In Strategic management, it is necessary to have an evaluation that is used to utilize feedback as input for the formation of new strategies in the future because today's challenges or problems are not necessarily the same as tomorrow. One evaluation technique is the balanced scorecard, this evaluation technique is generally used for evaluating profit organizations, but with the development of the present day this evaluation technique is often used by government organizations. Keywords : The Manpower Office of the city of Bandung, management strategy, evaluation